The Manufacture of GMP-Grade Bone Marrow Stromal Cells with Validated In Vivo Bone-Forming Potential in an Orthopedic Clinical Center in Brazil - Rhayra B. Dias; João A. M. Guimarães; Marco B. Cury; Leonardo R. Rocha; Elaine S. da Costa; Liebert P. Nogueira; Camila Hochman-Mendez; Anneliese Fortuna-Costa; Anna Karoline F. Silva; Karin S. Cunha; Sergio A. L. de Souza; Maria Eugênia L. Duarte; et al. (Stem Cells International)
In vitro-expanded bone marrow stromal cells (BMSCs) have long been proposed for the treatment of complex bone-related injuries because of their inherent potential to differentiate into multiple skeletal cell types, modulate inflammatory responses, and support angiogenesis. Although a wide variety of methods have been used to expand BMSCs on a large scale by using good manufacturing practice (GMP), little attention has been paid to whether the expansion procedures indeed allow the maintenance of critical cell characteristics and potency, which are crucial for therapeutic effectiveness. Here, we described standard procedures adopted in our facility for the manufacture of clinical-grade BMSC products with a preserved capacity to generate bone in vivo in compliance with the Brazilian regulatory guidelines for cells intended for use in humans. Bone marrow samples were obtained from trabecular bone. After cell isolation in standard monolayer flasks, BMSC expansion was subsequently performed in two cycles, in 2- and 10-layer cell factories, respectively. The average cell yield per cell factory at passage 1 was of 21.93±12.81×106 cells, while at passage 2, it was of 83.05±114.72×106 cells. All final cellular products were free from contamination with aerobic/anaerobic pathogens, mycoplasma, and bacterial endotoxins. The expanded BMSCs expressed CD73, CD90, CD105, and CD146 and were able to differentiate into osteogenic, chondrogenic, and adipogenic lineages in vitro. Most importantly, nine out of 10 of the cell products formed bone when transplanted in vivo. These validated procedures will serve as the basis for in-house BMSC manufacturing for use in clinical applications in our center.